The Potency of Fibre Feeds and Their Needs by The Ruminants in Indonesia - S. Reksohadiprodjo; H. Hartadi; D. Soetrisno; S. Padmowijoto; B. Suhartanto (Buletin Peternakan, 1995)
Artikel dalam bentuk hard copy